EXTRACT FROM Bixa orellana L. SEED: DEVELOPMENT OF BIODEGRADABLE PACKAGING AND BIOLOGICAL ACTIVITIES (Nativa, 2024)
ABSTRACT: Active biodegradable packaging with Bixa orellana extract has potential for producing new products that combine natural renewable use and food conservation. B. orellana seeds were collected and their extract was produced. The packages were produced and incorporated with different concentrations of B. orellana extract. Phytochemical parameters were tested in several groups of special metabolism; physicochemical for thickness, moisture, solubility, UV-Vis light transmission, color L*, a* and b*; biodegradability in soil and antifungal activity on Sclerotinia sclerotiorum, Colletotrichum acutatum and Colletotrichum gloeosporioides. The packaging showed potential for use as a new product for food, the large number of phytocompounds allows an active packaging, in addition to physicochemical characteristics of thickness, humidity and ideal solubility and use for foods that need protection at different wavelengths in the UV-Vis that deteriorate important characteristics of the product. Moreover, it demonstrated an effect with biodegradability of less than 40 days and antifungal activity on phytopathogenic fungi that cause deterioration in vegetables of agricultural interest.Keywords: Bixa genus; bixin; carotenoids; natural Polymer; norbixin; polymer matrix. Extrato das sementes de Bixa orellana L.: desenvolvimento de embalagens biodegradáveis e atividades biológicas RESUMO: Embalagens biodegradáveis ativas com extrato de Bixa orellana apresentam potencial para a produção de novos produtos que aliam o uso renovável natural e a conservação de alimentos. Sementes de B. orellana foram coletadas e o extrato produzido. As embalagens foram produzidas e incorporadas com diferentes concentrações do extrato de B. orellana. Foram testados parâmetros fitoquímicos em diversos grupos do metabolismo especial; físico-químicos para espessura, umidade, solubilidade, transmissão de luz UV-Vis, cor L*, a* e b*; biodegradabilidade em solo e atividade antifúngica sobre Sclerotinia sclerotiorum, Colletotrichum acutatum e Colletotrichum gloeosporioides. As embalagens demonstraram potencial para uso como novo produto para alimentos, o grande número de fitocompostos admite uma embalagem ativa, além de características físico-químicas de espessura, umidade e solubilidade ideais e uso para alimentos que necessitam proteção em diferentes comprimentos de ondas no UV-Vis que deterioram características importantes do produto. Além disso, demonstrou efeito com biodegradabilidade inferior a 40 dias e atividade antifúngica sobre fungos fitopatogênicos que causam deterioração em vegetais de interesse agrícola.Palavras-chave: gênero Bixa; bixina; carotenóides; matriz polimérica; norbixina; polímero natural.